A novel prognostic risk factor for patients undergoing radical prostatectomy: Triglyseride‐glucose index. Issue 5 (19th January 2021) - Horsanali, Mustafa Ozan; Eren, Huseyin; Dıl, Eyup; Kazaz, Ilke Onur; Uzun, Hakki
Abstract: Background: Obesity and metabolic syndrome are growing health problems in western countries. Recently reported triglyseride‐glucose (TyG) index is a reliable and accessible indicator of metabolic syndrome. TyG index could be used as a indicator of a prognostic risk factor for metabolic syndrome‐related cancers. Objectives: To investigate the prognostic role of TyG index on oncological outcomes in patients undergoing radical prostatectomy. Design, Setting and Participants: Data from 200 men who underwent radical prostatectomy were used. Outcome Measurements and Statsitical Analyse: TyG was calculated based on TyG index = Ln [TG (mg/dL) FPG (mg/dL)/2] formula. Patients were divided into two groups according to the 8.55 level as cut‐off value for TyG index. Laboratory results, oncological outcomes and survivals were comparised statistically between groups. Results: Mean ages of patients were 64.32 ± 6.1 years and median follow‐up time was 61.6 ± 35 (range 4‐140) month. Biochemical recurrens was observed in 42 (21%) patients. Positive correlation between TyG index, body mass index, waist circumference, prostate biopsy gleason score, clinical T stage, positive surgical margin, pathological T stage and biochemical recurrence were observed. There was no statistical significance in terms of survival between groups. Conclusion: Association between TyG index and prostate cancer may facilitate to predict unfavorable prognostic factors of radical prostatectomy. Increased TyG index may use as a predictive marker of positive surgical margin status before radical prostatectomy, BCR, advanced cT and pT stages after radical prostatectomy or worse biopsy gleason score in clinical practice.